Analysis of student difficulties in understanding the continuity of the function of differential calculus - Kus Andini Purbaningrum (STKIP PGRI Banjarmasin, 2019)
This study aims to determine the types of difficulties students have in understanding functional continuity in differential calculus subjects and the causes of these difficulties. The research subjects were second semester students of the Mathematics Education, FKIP Muhammadiyah University of Tangerang. This research is qualitative research, with data collection techniques namely tests and interviews. The results of the study obtained 3 types of student difficulties in completing continuity, namely: (1) difficulty in formulating a number line; (2) difficulties in carrying out continuity testing of functions; (3) difficulty in drawing graphs of function sketches. The causes of the problem are (1) the mastery of the basic mathematical concepts learned in the first semester is not well recognized; (2) less able to answer the meaning of the questions in the question; (3) Less time is better used to explore the material being studied.